Does it work? Implicit bias training for postgraduate program directors - Gruber, Jackie; Condon, Amanda (Canadian Medical Education Journal, 2023)
Implication Statement One element to address health disparities and historical injustices of systemically excluded groups is to examine selection processes. Implicit association testing for selection committees is suggested as one intervention to address bias in selection and is used for Undergraduate Medical Education at the University of Manitoba. Our study demonstrated that implicit bias training for PDs in isolation has minimal impact on addressing bias within resident selection. This training must occur as part of a systemic institutional approach to address bias in resident selection. Programs should consider a multipronged and sustained approach when committing to diversifying postgraduate medical education programs.